The Sertifikasi BPOM dan Sertifikasi Halal Terhadap Loyalitas Konsumen Ditinjau dari Kepercayaan Konsumen Mie Gacoan Kudus - Jauhar, Muhammad Adib; Kusuma, Aryanti Muhtar (ITB AAS INDONESIA Surakarta, 2026)
This study aims to examine how BPOM certification and halal certification influence consumer loyalty, with consumer trust acting as a mediating variable in the context of Mie Gacoan Kudus. A quantitative approach was employed by conducting a survey of 100 consumers who had purchased and consumed Mie Gacoan products. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of SPSS. The findings indicate that BPOM certification and halal certification jointly contribute to strengthening consumer loyalty. When examined individually, both certifications show a positive effect on loyalty, although halal certification demonstrates a stronger influence than BPOM certification. The results further reveal that halal certification and consumer loyalty significantly shape consumer trust, whereas BPOM certification does not exhibit a meaningful effect on trust. These findings suggest that consumer trust is more strongly driven by halal assurance and repeated consumption experiences rather than by administrative aspects of food safety alone. This study highlights the importance of consumer trust in linking product certification and loyalty, particularly within the fast-food culinary industry in regions with a predominantly Muslim consumer base. The results are expected to provide practical insights for culinary business practitioners in developing trust-based strategies to sustain long-term consumer loyalty.